APPROACHES TO EARLY CARE AND EDUCATION IN MALAYSIAN CHILD CARE CENTRES (TASKA): SUPPORTING INFANT AND CHILD DEVELOPMENT IN ACCORDANCE WITH PARENTAL ASPIRATION - NURIN JAZLINA AZMEE; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
The teaching and learning strategies used in TASKA are examined in this study, with a focus on how they support kids' cognitive, emotional, social, and physical development. Important theoretical stances that inform successful teaching methods in early childhood education, such as behaviourism theory and Piaget's play-based learning theory, are incorporated into the conversation. However, there are a number of implementation-related issues, such as inadequate training for teachers, a lack of instructional resources, budgetary limitations, and excessive workloads. Because they place a high value on teacher quality, safety, cleanliness, and open communication between the home and the school, parents' expectations also have an impact on educational practices. Improvements including ongoing professional development for teachers, the supply of innovative and secure educational resources, reduced teacher-to-child ratios, and improved parent collaboration are suggested as ways to improve the quality of teaching and learning at TASKA.